The Impact of Ownership Structure on Corporate Social Responsibility - Waluyo, Waluyo (Opción, 2019)
The prime objective of the current study is to explore the linkbetween ownership structure and corporate social responsibility byusing the panel data methodology. Data of 5 years (2012-2016) iscollected from the firm's audited account. The findings of the studyhave shown a strong link between ownership structure and audit fee.In conclusion, the directors’ ownership structure of the organizationmay offer ascent to legitimacy gaps. Distinctive shareholders mayrequest diverse disclosures and the interest is more significant tooutsiders, due to the detachment between of administration andholders geographically, hold a high extent of shares.